Malaysian parents’ perceptions of children’s play - Badzis, Mastura (Unit Penyilidikan Pendidikan Asas, Pusat Pengajian Ilmu Pendidikan, Universiti Sains Malaysia, 2004)
Play is children’s natural tendency and widely regarded as providing a rich context for children’s learning in the field of early childhood education. A commitment to play has underpinned many traditional approaches to early childhood curriculum. Pertaining to the matter of partnership with parents, there was evidence indicating that many pre-school educators are resisting the push by parents towards increasingly formal and academic pre-school education. Parents did not favour play as an activity linked to the children’s learning. This study examined the perceptions of Malaysian parents concerning their perceptions of children’s play in relation to pre-school classroom practice. Thirty parents of 4 to 6 years old children attending five different types of pre-school settings were interviewed about their perceptions on play as pedagogical tools, reasons for sending their children to a certain type of pre-school; and their preferred activities for the children either more academic or play-based. The evidence from parents’ responses implies that only few parents considered play to be the appropriate way for children’s learning. Many parents are at loss to see educational functions of play and the vast majority of them bought that children get enough play at home while at school they should learn the basic skills of 3R’s performance in a formal learning environment. As a result of the findings, some implications have been advocated concerning the need for rethinking the practice in Malaysian pre-school for improving the policy of educating young children by giving emphasizes on school-parent partnership. As parents play important roles in determining educational experience for their children, they should be given opportunity of developing their knowledge regarding developmentally appropriate practice for young children’s educational experiences.